Intelligent road traffic control system using decision model - Lee, Keng Sheng (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The normal function of traffic lights requires sophisticated control and coordination to ensure that traffic moves as smoothly and safely as possible and that pedestrians are protected when they cross the roads. The decision model used in the old-fashioned technology is of static traffic assignment (STA) in which traffic lights are configured to turn on the green color after a given period of time, but this may very well vary depending on traffic values and region. Such legacy system may be fair in equally allocating time for every junction, but this can caused congestion traffic especially in the prosper region. Dynamic traffic light control systems on the other hand are more appropriate for the crowded traffic we faced everyday as they have been developed specifically to be able to adapt their settings to traffic conditions. This intelligent traffic control system is expected to improvise the normal traffic control to reduce the congested traffic condition by proposing a suitable decision model based on the different traffic condition. This paper will be focusing on simulating the decision model of the dynamic traffic light control system and the results will be used for comparisons. The variable used for comparison is the average vehicle delay time and the results will be used to measure based on the standards define by level of service (LOS).